Respuesta :

Answer:  [tex]\bold{b)\quad \dfrac{17}{36}}[/tex]

Step-by-step explanation:

[tex].\quad \dfrac{1}{6}\bigg(2\dfrac{1}{3}-\dfrac{3}{4}\bigg)+\dfrac{5}{24}\\\\\\=\dfrac{1}{6}\bigg(\dfrac{7}{3}-\dfrac{3}{4}\bigg)+\dfrac{5}{24}\\\\\\=\dfrac{1}{6}\bigg(\dfrac{28}{12}-\dfrac{9}{12}\bigg)+\dfrac{5}{24}\\\\\\=\dfrac{1}{6}\bigg(\dfrac{19}{12}\bigg)+\dfrac{5}{24}\\\\\\=\dfrac{19}{72}+\dfrac{5}{24}\\\\\\=\dfrac{19}{72}+\dfrac{15}{72}\\\\\\=\dfrac{34}{72}\\\\\\=\large\boxed{\dfrac{17}{36}}[/tex]

Answer:

the answer is b

Step-by-step explanation:

pictured and shown

Ver imagen meredith48034